Recovery of Historical Memory in Fiction Series through Social Networks. The case of Spain and Chile - Chamorro Maldonado, Miguel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
The time living fiction series on television is auspicious because its subject, technical and professional quality, and an example of this is the series of historical character. Its production involves not only designing the product for the small screen, but also do charitable work through the distribution of their content through social networks, generating an active contact with viewers who are both followers in the respective platforms digital. In this paper a study on the recovery of historical memory in fiction series through Internet social networks develops. The sample corresponds to the Spanish series Amar es para siempre and Cuéntame Cómo Pasó, which it has been applied to the speech content analysis to understand what variables, users delve on the recovery of memory in social networks.